Factors that affecting claim rejection at Takaful Ikhlas Sdn Bhd within 2007 to 2009 / Muhammad Nasyar Abdul Rahman - Abdul Rahman, Muhammad Nasyar (Faculty of Business and Management, 2011)
Claim rejection is designed to present about the reality life process in insurance industry in facing the claim that they rejected. Claim rejection is important thing that an insurance company need to handle because from that they gain the profit and suffer a loss. Then, there will have a dispute between the insurance company and insured. Claim rejection occurs every year and there have reason in rejecting the claim and it is whether large or small claims. To reject some claim case, there need a discussion between members staff and provide evidence to proceed rejection because a claim is rejected in writing filed with the court, and a judge shall approve or disapprove the rejection if the claimant protests. If a claim is not acted upon it may be presumed to be approved in most states. Therefore, the research is conducted to study the factors affecting claim rejection at Takaful Ikhlas Sdn Bhd within a period 2007 to 2009. Overall, most of factor agreed that they are non-disclosure, fraud, exclusion, or warranty is frequently occurs in claim rejection.